Alien honeybees increase pollination risks for range-restricted plants - Norfolk, Olivia; Gilbert, Francis; Eichhorn, Markus P. (Wiley, 2018)
Aim:Range-restricted species are of high conservation concern and the way in which they interact with more widespread species has implications for their persistence. Here we determine how the specialisation of mutualistic interactions varies with respect to the geographic range size of plants and pollinators and assess how they respond to the introduction of the alien honeybee. We also compare network characteristics (connectance, specialisation, nestedness) between an invaded low mountain and non-invaded high mountain network. Location:St Katherine Protectorate, South Sinai, Egypt.